2020
DOI: 10.4049/jimmunol.1901457
|View full text |Cite
|
Sign up to set email alerts
|

H and L Chain Affinity Maturation and/or Fab N-Glycosylation Influence Immunoreactivity toward Neutrophil Extracellular Trap Antigens in Rheumatoid Arthritis Synovial B Cell Clones

Abstract: We previously showed that anti-neutrophil extracellular trap (NET) rheumatoid arthritis (RA)-rmAbs derived from CD19 + B cells within RA human synovial tissues frequently react against NETs. In this study, we aimed to characterize the importance of affinity maturation via somatic hypermutation (SHM) within the Ig variable H (VH) and variable L (VL) chains and Fab-N-linked glycosylation in RA synovial B cell clones reactive to NETs and NET-derived Ags such as citrullinated histones. Selected anti-NET RA-rmAbs d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…In another study, Corsiero et al has shown that N-linked glycosylation in the Fab region of Anti-NET RA-Antibodies were largely responsible for their immunoreactivity. Removing the glycans from the antibodies resulted in a 90% decrease in its reactivity towards citrullinated histone H2B [29]. Findings like these may have major implications on future therapies for autoimmune diseases like rheumatoid arthritis.…”
Section: Modifying Glycosylation For Immunity Refittingmentioning
confidence: 85%
“…In another study, Corsiero et al has shown that N-linked glycosylation in the Fab region of Anti-NET RA-Antibodies were largely responsible for their immunoreactivity. Removing the glycans from the antibodies resulted in a 90% decrease in its reactivity towards citrullinated histone H2B [29]. Findings like these may have major implications on future therapies for autoimmune diseases like rheumatoid arthritis.…”
Section: Modifying Glycosylation For Immunity Refittingmentioning
confidence: 85%
“…Results from previous studies have provided initial evidence that N-glycans can influence many properties of Fab. For example, it was found that the N-linked glycosylation, introduced by somatic hypermutation (SHM) in the V H /V L regions of the autoantibodies isolated from patients with rheumatoid arthritis, could modulate the binding of Fab to the antigen citrullinated histone (cit-H2B) [54]. In another example, the antigen binding was tested using several anti-adalimumab and anti-infliximab antibody mutants, in which the naturally occurring Fab glycans were removed.…”
Section: Monoclonal Antibodiesmentioning
confidence: 99%
“…This non-conserved glycosylation has been shown to negatively influence the avidity profile of ACPA and seems to be the result of the introduction of new N-glycosylation sites during the extensive somatic hypermutation process [ 116 , 117 ]. In a recent study, the importance of Fab-glycosylation for the recognition of NET-antigens and citrullinated histones was demonstrated [ 118 ]. Interestingly, IgM ACPA do not appear to have this characteristic Fab-glycosylation [ 119 ].…”
Section: Influence Of Glycosylation On the Properties Of Autoantibodi...mentioning
confidence: 99%